“Always into the unknown”: the mystery in the reflective prose of Juan Ramón Jiménez and José María Eguren - Olivé, Laia (2026)
With similar concerns and interests, and in parallel with their poetry, Juan Ramón Jiménez and José María Eguren wrote reflective prose works on common themes such as art, beauty, and death. These texts show special attention to the unknown, which arises when the invisible (or spiritual) comes into contact with the visible (or material). This paper compares, for the first time, the reflective writings of these two poets. It closely examines their treatment of mystery and some of its manifestations: nature, death, dreams, children, women, and the self.